Compare Mean Blood Loss in Patients Undergoing Tonsillectomy with and without Tranexamic Acid - Muhammad Asif Ashraf, Ishfaq Ahmed, Sanaullah Bhatti, Deepak Rai, Sara Samad Qureshi, Rana Farrukh Tasleem (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Tonsillectomy is one of the most common surgeries in ENT department and bleeding is one of the most serious complications related to tonsillectomy. Tranexamic acid is a plasminogen inhibitor which has been successfully used to control bleeding in a variety of surgeries. Objective: The objective of this study is to compare mean blood loss in patients undergoing tonsillectomy with and without Tranexamic acid. Study Design: Randomized controlled trail Setting: This study was carried out at the Department of ENT Jinnah Hospital Lahore Sample Technique: Non-probability, consecutive sampling Study Duration: The study was done in 6 months after the approval of synopsis [March 8, 2017 till September 8, 2017] Materials and Methods: Sixty Patients were randomly divided into 2 equal groups using lottery method in group-A and group-B. Patients in Group-A received tranexamic acid after induction intravenously as 15 mg/kg (single bolus dose) over 10 min. Patients in group B were served as control group and they did not receive tranexamic acid before tonsillectomy. All surgeries were carried out by a single consultant having more than 5 years of experience after post-graduation. Blood loss was measured by researcher himself as per operational definition. Results: The mean age of cases in Tranexamic group was 19.70 ± 12.12 years while in control group was 21.53 ± 15.44 years. In Tranexamic acid group there were 18(60%) male and 12(40%) female cases while in control group there were 21(70%) male and 9(30%) female cases. The mean blood loss in Tranexamic acid group were 30.27 ±8.85 ml and in control group was 67.67 ± 14.91 ml. The mean blood loss was significantly less in Tranexamic acid group as compared to control group, p-value < 0.05. Conclusion: The mean blood loos in cases with Tranexamic acid were significantly lower as compared to control group. So in future every patient selected for tonsillectomy must be given TXA to reduce the blood transfusion and related complications of the patients. Keywords: ENT, Tonsillectomy, Bleeding, blood transfusion, Tranexamic acid